PENGARUH KUALITAS LAYANAN, PERSEPSI HARGA, DAN PROMOSI PENJUALAN TERHADAP KEPUTUSAN PEMBELIAN PT TIARA INDAH ABADI PIAGGIO VESPA GIANYAR - Kadek Yunita Wendistha; Daniel Manek (Jurnal Bakti Saraswati (JBS), 2024)
The purchasing decision is a complex process that involves identifying needs, evaluating alternatives, selecting products or services, and making a purchase. There are several factors that influence purchasing decisions, such as service quality, price perception, and sales promotion. This study aims to determine and analyze the influence of service quality, price perception, and sales promotion on purchasing decisions at PT Tiara Indah Abadi Piaggio Vespa Gianyar. The population of this study is 106 consumers of PT Tiara Indah Abadi Piaggio Vespa Gianyar in September 2023. The study uses a census sampling technique, and the data collection methods include observation, interviews, and questionnaires. The study uses multiple linear regression analysis with SPSS version 26 for windows. The results show that service quality and price perception variables have a positive and significant effect on purchasing decisions, while the sales promotion variable has a negative and insignificant effect on purchasing decisions.